Covid-19 Pandemic and Childhood Cancer: Lessons Learnt from a Pediatric Oncology Unit in a Developing Country - Manasa Kakunje; Niteesh Bharadwaj; Kenson Sam Alex; Vandana Bharadwaj; Anand Prakash (Asian Pacific Journal of Cancer Care, 2023)
Background: COVID-19 pandemic has caused unprecedented challenges to healthcare delivery globally. Children with cancer are a vulnerable group given their immunosuppressed state. There is paucity of data regarding the organisation of pediatric cancer care and outcomes of children with cancer who developed COVID-19 infection. We describe the organisation of care in a Pediatric Oncology unit in a tertiary care hospital in South India and describe the clinical profile and outcomes of children with cancer who were diagnosed with COVID-19 infection. Methods: This was a retrospective chart review of all children admitted to the pediatric oncology unit and diagnosed with COVID-19 infection between March 2020 and October 2020. Descriptive statistics were calculated. Results: A total of 144 children were on active chemotherapy during the study period. Of these, Nine (6.2 %) were diagnosed with COVID-19. Fever and cough were the predominant symptoms. Majority (88%) had mild symptoms. COVID-19 was positive at cancer diagnosis in 22%. PICU care was required for 33%, but for non-covid related concerns. Recovery from Covid-19 was seen in 88%. Chemotherapy administered during or after Covid-19 infection was well tolerated. Co-existent sepsis or CMV infection resulted in severe symptoms leading to mortality and this was not related to severe covid related symptomatology. Conclusions: In our study, majority of children with cancer who developed covid-19 had mild symptoms and recovered uneventfully. Chemotherapy should not be delayed in children with active cancer. The overall outcomes of pediatric oncology care during the pandemic are reassuring.